2008
DOI: 10.1590/s1516-35982008000500013
|View full text |Cite
|
Sign up to set email alerts
|

Influência do óleo de linhaça sobre o desempenho e a qualidade dos ovos de poedeiras semipesadas

Abstract: RESUMO -O experimento foi conduzido para avaliar a influência da adição de óleo de linhaça em substituição ao óleo de soja em rações para poedeiras semipesadas sobre o desempenho e a qualidade interna e externa dos ovos. poedeiras da linhagem Bovans Godline com 29 semanas de idade, distribuídas em seis tratamentos, que consistiram de uma dieta controle (sem óleo vegetal) e de cinco dietas contendo 0,0; 0,5; 1,0; 1,5 e 2,0% de óleo de linhaça em substituição, respectivamente, a 100, 75, 50, 25 ou 0% do óleo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
6
2
4
Order By: Relevance
“…The obtained values are compatible with those of second-cycle layers (Table 2). These results are different from those of Costa et al (2008), who found a linear effect of different soybean oil levels on egg production, whereas canola oil did not influence this parameter. Rodrigues et al (2005) found that egg production decreased when soybean oil was not supplemented in the feed, and that it increased as soybean oil was included in the diet, being the highest at the maximum level of soybean oil inclusion (8%).…”
Section: Egg Productioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The obtained values are compatible with those of second-cycle layers (Table 2). These results are different from those of Costa et al (2008), who found a linear effect of different soybean oil levels on egg production, whereas canola oil did not influence this parameter. Rodrigues et al (2005) found that egg production decreased when soybean oil was not supplemented in the feed, and that it increased as soybean oil was included in the diet, being the highest at the maximum level of soybean oil inclusion (8%).…”
Section: Egg Productioncontrasting
confidence: 99%
“…Some authors did not find any differences in the performance of layers fed different oil sources (Yu & Sim, 1987;Hargis et al, 1991;Nash et al, 1996). Costa et al (2008) did not observe worse performance in heavy layers fed a diet containing 2% linseed oil as compared to those fed a control diet based on corn and soybean meal. Also, Baucells…”
Section: Introductionmentioning
confidence: 96%
“…When oil is added to the diet, the fatty acid synthesis is reduced and the bird has more energy for productive performance (Costa et al, 2008). However, although the levels of methionine, linoleic acid and oil have increased with the inclusion of canola meal in the diet, egg weight showed an increasing quadratic response up to the level of 30% of canola meal, with subsequent reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Sim & Bragg (1977), Holland et al (1980), Hargis et al (1991) e Mori et al (1999) descreveram que a inclusão de óleos vegetais ricos em ácidos graxos poliinsaturados na ração de poedeiras pode reduzir a concentração de colesterol na gema e no plasma. No entanto, os resultados encontrados na literatura são contraditórios (Costa et al, 2008).…”
Section: Introductionunclassified